IMPLEMENTASI METODE ANALYTICAL HIERARCHY PROCESS PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PRODUK PERAWATAN KULIT - Fransiska Luminovita; Tony Tony (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Skin care is a series of treatments that can maintain the beauty and healthy of the skin by using skin care products such as serum, moisturizer and cream. It is very important to choose skin care products according to skin type, because each skin type has its own problems. Skin care that is not in accordance with the type of facial skin will cause problems or worsen skin conditions. Currently, many people still lack information about skin care products based on their respective skin types, so people are confused about choosing the right skin care products. Naavagreen Natural Skincare is a beauty treatment center for facial skin with natural ingredients under the supervision of a doctor who provides various solutions for skin types. The system is made based on a website using the PHP programming language and MySQL database as database management. The results of the AHP (Analytical Hierarchy Process) calculations are to produce the best alternative for each skin type.